DOES SIZE MATTER? THE MODERATING ROLE OF FIRM SIZE ON GREEN PRACTICE AND CORPORATE VALUATION - Alma Athif Fabian; Tantina Haryati (Universitas Riau, 2026)
This research aims to examine how green accounting, green intellectual capital, as well as green innovation influence corporate value, while incorporating firm size as a moderating factor in non-cyclical consumer companies registered on the Indonesia Stock Exchange during 2021–2024. This research is motivated by the escalating concern of sustainability and the evolving viewpoint of investors in assessing companies, where not only financial metrics are considered by the investors, but also the environmental practices used by the company. Nevertheless, prior research has produced contradictory findings concerning the influence of sustainability-related practices on corporate value. This research applies a quantitative method utilizing panel data regression analysis. The findings reveal that green accounting does not significantly affects firm value, because most companies exhibit similar environmental performance, while investors remain more focused on financial information than environmental disclosures. Green intellectual capital negatively influences firm value, whereas green innovation contributes positively affects firm value. Furthermore, firm size is not capable of moderating the effects of green accounting, green intellectual capital, and green innovation on firm value. The results imply that companies should effectively implement and communicate sustainability initiatives to investors